Visual Thinking Strategies in medical education: a systematic review - Ana Rita Cerqueira; Ana Sofia Alves; Matilde Monteiro-Soares; Dabney Hailey; Domingos Loureiro; Sofia Baptista (BMC Medical Education, 2023)
Abstract Background Arts-based pedagogical tools have been increasingly incorporated into medical education. Visual Thinking Strategies (VTS) is a research-based, constructivist teaching methodology that aims to improve visual literacy, critical thinking, and communication skills through the process of investigating works of art. Harvard Medical School pioneered the application of VTS within medical education in 2004. While there are several studies investigating the use of VTS, there is a need to systematically assess the different programs that exist for medical education and their efficacy in improving relevant clinical skills. This systematic review aims to critically analyse the available evidence of the effectiveness of VTS in medical education to guide future research and provide a framework to adapt medical curricula. Methods A systematic search of PubMed, PsycINFO, and Cochrane CENTRAL databases (through November 2022) was conducted to identify studies of VTS-based interventions in undergraduate and postgraduate medical education. Two reviewers independently screened citations for inclusion criteria, extracted data, and assessed risk of bias. The extracted data was then narratively synthesized. Results Of 5759 unique citations, 10 studies met the inclusion criteria. After reference review, one additional study was included. Therefore, 11 studies were included in our review. Of these, eight reported VTS-based interventions for undergraduate medical students and three reported interventions in residency training, specifically in dermatology and ophthalmology. The main goal of most studies was to increase observational or visual diagnostic skills. Three of the studies in undergraduate medical education and two in postgraduate achieved a statistically significant improvement in observational skills in post-course evaluations. Some studies reported increased tolerance for ambiguity and empathy. Conclusions Although the studies varied considerably in study design, learning objectives, and outcomes, findings consistently indicate that the VTS approach can serve as a vehicle to develop crucial clinical competencies, encouraging more in-depth visual analysis that could be applied when observing a patient. Despite some limitations of the included studies (lack of control groups, self-selection bias, or non-standard outcome measures), the results of this review provide support for greater inclusion of VTS training in the medical curriculum.